Observasi Biodiversitas Burung dan Habitatnya di Kawasan Cagar Budaya Nasional (KCBN) Candi Muaro Jambi - Riska Afrilia; Khairatinisa Khairatinisa; Tedjo Sukmono; Nisrina Salsabila; Mohammad Ekki Hadian (MAN 4 Kota Pekanbaru, 2025)
Birds play an important role in ecosystem as pollinators and seed dispersers, so avian diversity can serve as an indicator of environmental quality. This study was at Muaro Jambi Temple, a National Cultural Heritage Area (KCBN), and began with a presentation on observation techniques, field identification, and understanding of ecological characteristics. The survey was conducted in two observation zones, namely the core zone and the buffer zone, using the point count method. Observers stood at specific points within the habitat and recorded bird sightings during defined time periods. Observations were conducted for one week in August 2025, from 6:00 a.m. to 9:00 a.m. and 3:00 p.m. to 6:00 p.m. The study recorded 79 species comprising a total of 327 individual birds. The Shannon-Wiener diversity index (H’) of 3.75 indicates a very high level of diversity in the area. Several species found are protected, including frugivorous and pollinating birds. Based on the IUCN Red List, identified species include the Java Sparrow (Vulnerable), the Ciblek/Perenjak (Near Threatened), and a numerous other species categorized as Least Concern. These findings emphasize the importance of conservation efforts at KCBN Muaro Jambi to preserve habitats and maintain the ecological function of birds.